Less is more – retrospective comparison of shoulder strength and range of motion between conventional and muscle-sparing harvesting technique of a latissimus dorsi flap - Müller-Seubert, Wibke; Scheibl, Karsten; Bührer, Gregor; Möbius, Cornelia; Ludolph, Ingo; Horch, Raymund E.; Arkudas, Andreas (Journal of Plastic Reconstructive and Aesthetic Surgery, 2021)
Background: The muscle-sparing latissimus dorsi flap poses an alternative to the conventional latissimus dorsi flap when a defect requires a smaller flap volume with a long vascular pedicle. The aim of the study was to analyze the functional outcome following muscle-sparing versus conventional harvest of a latissimus dorsi flap. Material and Methods: Patients who received a muscle-sparing latissimus dorsi muscle flap transplantation (group 1) and patients with a complete latissimus dorsi muscle flap harvest (group 2) for defect reconstruction at the University Hospital of Erlangen between 2007 and 2016 were examined. The evaluation included a physical examination with the measurement of strength and range of motion of the shoulder of both the donor side as well as the nonoperated side. Furthermore, the DASH score was evaluated. Additionally, patients in group 1 received a neurophysiological examination. Results: The DASH score did not show statistically significant differences between both groups. Both strength (p = 0.031) and range of motion (p<0.05) of the shoulder of the donor side were statistically significantly lower than the nonoperated side in group 2, while no difference was found in group 1. The neurophysiological examination in group 1 showed a reduced nerve conduction velocity of the donor side as compared to the nonoperated side in most patients (60% and n = 3). Conclusion: Harvesting the muscle-sparing latissimus dorsi flap leads to less functional impairments of the shoulder than harvesting the complete latissimus dorsi flap.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Defect reconstruction; Functional impairment; Latissimus dorsi flap; Muscle sparing latissimus dorsi flap